ChemInform Abstract: Generation of Arylated Quinones by Iron‐Catalyzed Oxidative Arylation of Phenols: Formal Synthesis of Phellodonin, Sarcodonin ε, Leucomelone and Betulinan A. Issue 34 (26th August 2014) - Deb, Arghya; Agasti, Soumitra; Saboo, Tapish; Maiti, Debabrata
Abstract In a few cases NaOH is found advantageous over K2CO3.